Peranan Program TPQ dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di SMP Negeri 18 Padang - Ramadan, Syahril; Wardefi, Riza (Lembaga Yasin AlSys, 2025)
This study is motivated by the still low ability of students to read the Al-Qur'an, thus a program for the Religious Education Center (Taman Pendidikan Al-Qur'an, TPQ) is needed to improve these skills at SMP Negeri 18 Padang. The purpose of this research is to analyze the planning and implementation stages of the TPQ program and to identify the factors that influence its success. The method used is qualitative research with a field research approach, involving five informants selected through purposive and snowball sampling techniques. Data were collected through observation, interviews, and documentation, and were subsequently analyzed systematically with reference to the stages of data collection, reduction, presentation, and conclusion drawing. The results indicate that the planning stages of the TPQ program include the determination of objectives, materials, and methods. The implementation of the program uses the Iqro' and Qiro'ati methods, which consist of initial, core, closing activities, and evaluation stages. The success factors of the program are influenced by internal factors, namely the quality of learning and students, as well as external factors including support from parents, teachers, schools, and peers. The TPQ program has proven to play an important role in improving students' abilities to read the Al-Qur'an.